Factores socioculturales desencadenantes de la violencia de género en la comunidad LGBTTIQ de la ciudad de Machala. año 2021 - Brito Rodríguez, Sixto Fernando; Jadán Robalino, Mara Betzabeth (Machala : Universidad Técnica de Machala, 2022)
The present investigation seeks to identify those sociocultural factors that trigger gender violence in the LGBTTIQ community of the city of Machala, according to the United Nations Organization UN the term is used to refer to the fact that on the basis of gender they are violated. human rights, expressed in various situations and social institutions, to mention. The State, religion, world of work, education, culture, coexistence in public spaces, among others. The LGBTTIQ community in the city of Machala has been exposed by various social elements that normalize and reproduce this violence. The National Institute of Statistics and Census in its first investigation on living conditions, social inclusion and human rights of the LGBTI population in Ecuador, in which 2,805 people from 10 cities in the country participated, including Machala, the results show that 65% of the community has been violated in the public space, 40% has been discriminated against in the educational field, 43.8% in the workplace and 71.4% have been excluded from the private space. The objective of this research is to identify which sociocultural factors trigger gender violence towards the LGBTTIQ community in the city of Machala, with the purpose of interpreting and describing elementary issues that structure it in social circles ranging from the nature of hate , from prejudice, discriminatory acts to social exclusion in order to promote friendly environments towards sexual diversity in the different spaces that these human groups can be incorporated or are already incorporated. The approach used in the research process is of a qualitative nature, for which techniques and instruments such as in-depth interviews and focus groups were applied to collect information, which contributed to analyze and interpret lived experiences and relevant aspects around the situation of violence. The study is part of basic research by providing objective information on the dimensionality of gender violence with the purpose of increasing knowledge about this social phenomenon for the generation of academic contributions that can be used by various investigations.
La presente investigación busca identificar aquellos factores socioculturales desencadenantes de la violencia de género en la comunidad LGBTTIQ de la ciudad de Machala, de acuerdo con la Organización de las Naciones Unidas ONU el término se utiliza para referenciar que sobre la base del género se vulneran derechos humanos, expresadas en diversas situaciones e instituciones sociales, a mencionar, el Estado, religión, mundo laboral, educación, cultura, convivencia en espacios públicos, entre otros. La comunidad LGBTTIQ en la ciudad de Machala se ha visto expuesta por varios elementos sociales que normalizan y reproducen esta violencia. El Instituto Nacional de Estadísticas y Censos en su primera investigación sobre condiciones de vida, inclusión social y derechos humanos de la población LGBTI en Ecuador, en la que participaron 2.805 personas de 10 ciudades del país, entre ellas Machala, en los resultados se evidencia que 65% de la comunidad ha sido violentada en el espacio público, el 40% ha sido discriminada en el ámbito educativo, el 43,8% en el ámbito laboral y el 71,4 ha sido excluido del espacio privado. El objetivo de esta investigación es identificar qué factores socioculturales desencadenan la violencia de género hacia la comunidad LGBTTIQ en la ciudad de Machala, con el propósito de interpretar y describir cuestiones elementales que la estructuran en los círculos sociales que van desde la naturaleza del odio, del prejuicio, actos discriminatorios hasta la exclusión social con la finalidad de fomentar ambientes amigables hacia la diversidad sexual en los distintos espacios que se puedan incorporar o ya estén incorporados estos grupos humanos. El enfoque utilizado en el proceso de investigación es de carácter cualitativo para lo cual en el levantamiento de información se aplicó técnicas e instrumentos como las entrevistas a profundidad y grupos focales que contribuyeron a analizar e interpretar experiencias vividas y aspectos relevantes en torno a la situación de violencia. El estudio se encuadra en una investigación básica al proporcionar información objetiva sobre la dimensionalidad de la violencia de género con el propósito de incrementar los conocimientos sobre este fenómeno social para la generación de aportes académicos que puedan utilizarse por diversas investigaciones.
Keywords: FACTOR SOCIOCULTURA; LGBTTIQ; VIOLENCIA; GENERO